2014
DOI: 10.2478/pjvs-2014-0014
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione and glutathione-related enzymes in rats exposed to dimethoate and/or pyrantel

Abstract: The study was undertaken to examine the effect of single and combined administration of dimethoate (an OP insecticide) and pyrantel embonate (an anthelmintic agent) on the concentration of reduced glutathione (GSH) and the activity of glutathione peroxidase (GPx) and glutathione reductase (GR) in rats. Dimethoate (Group I) was administered to rats at a dose of 1/10 LD 50 for 5 consecutive days and pyrantel embonate (Group II) at a dose of 1/5 LD 50 for 3 consecutive days. The animals of group III were given bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
4
1
Order By: Relevance
“…A decrease in GSH/GSSG was observed as a result of exposure to OPs, carbamates and paraquat [ 7 , 9 , 23 , 24 , 27 , 39 – 41 ]. However, unlike our results, studies that have analyzed GSH and GSSG specifically in erythrocytes after exposure to OPs (as was done in the present study) reported high levels [ 42 , 43 ]. Particularly, differences in the GSH and GSSG responses depend not only on the type of sample analyzed, but also the type of OPs involved, and the duration of exposure [ 42 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A decrease in GSH/GSSG was observed as a result of exposure to OPs, carbamates and paraquat [ 7 , 9 , 23 , 24 , 27 , 39 – 41 ]. However, unlike our results, studies that have analyzed GSH and GSSG specifically in erythrocytes after exposure to OPs (as was done in the present study) reported high levels [ 42 , 43 ]. Particularly, differences in the GSH and GSSG responses depend not only on the type of sample analyzed, but also the type of OPs involved, and the duration of exposure [ 42 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The higher values to GSH and GSSG in the not exposed group, suggests that exposure to pesticides (regardless of the duration in years of use) affects human health, since the only group that maintained its functional antioxidant activity was not exposed group. On the other hand, the low levels of GSH and GSSG markers in exposed subgroups may be due to the low antioxidant defense induced by chronic exposure to pesticides, as reported by Spodniewska et al [ 42 ] and Georgiadis et al [ 43 ]. Conversely, other studies show that pesticide exposure may increase the GR activity, which converts GSSG to GSH, as an adaptation of the organism to prevent permanent oxidative damage [ 26 , 34 , 41 ].…”
Section: Discussionmentioning
confidence: 94%
“…An endocrine disrupter pesticide endosulfan has been shown to reversibly inhibit human CYP3A4 enzyme [56]. Dimethoate pretreatment in rats caused an increase in the activities of glutathione peroxidase and glutathione reductase, as compared to the control animals [57]. A recent study has also shown that a new fungicide propiconazole inhibited P-glycoprotein (P-gp) transporter protein with an inhibition potency similar to erythromycin [35].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a very limited number of studies concern the consequences caused by the co-administration of pesticides and medicaments (Babu et al, 2006;Buyukokuroglu et al, 2008), and only individual ones focus on the oxidative stress (Spodniewska et al, 2014). A decrease in the contents of both vitamin A and E was noted in our study following the enrofloxacin and chlorpyrifos co-administration.…”
Section: Pollution Of the Environment With Various Xenobiotics Is A Mmentioning
confidence: 81%